Perawatan dan Perbaikan Alat Reach Stacker (RS) PT. Pelabuhan Indonesia IV (PERSERO) Cabang Kendari - Emil Salim; Muh. Alfito Ramadhan; Muhammad; Aminur (Program Pendidikan Vokasi Teknik Mesin, 2022)
Maintenance is an activity or action to maintain and care for equipment to ensure the availability and reliability of the equipment for the stability of the production process. Reach Stacker is one of the lifting equipment that has a very important role in helping port loading and unloading services. This study aims to determine the types of damage to the equipment and also to increase the readiness of technicians or management in handling maintenance on equipment using preventive maintenance, predictive maintenance, and corrective maintenance methods. From the results of the analysis, the damage that often occurs to the reach stacker tool is divided into several main component groups, namely the engine group, electrical group, hydraulic group, drive group, and chassis group. each component to increase the readiness of technicians in dealing with failure or damage problems that occur in the equipment and the port party must quickly take steps or actions in the main maintenance process in replacing spare parts due to failures in equipment components.